Factors Affecting Health Care Utilization in OEF/OIF Veterans: The Impact of PTSD and Pain. Issue 1 (1st January 2016) - Lang, Katie P.; Veazey-Morris, Katherine; Berlin, Kristoffer S.; Andrasik, Frank
ABSRACT: Objectives: Returning Operation Enduring Freedom and Operation Iraqi Freedom veterans are at a high risk for physical and mental health symptoms including pain (90%) and post-traumatic stress disorder (PTSD) (58%). These often present concurrently and result in many health problems, functional impairments, and overall poor rehabilitation. To address postdeployment health, effective and efficient allocation of health care resources is needed. Methods: Retrospective study of 144 veterans who completed a second-level screening in the Polytrauma clinic. Veterans completed the PTSD Checklist-Civilian Version. Their pain rating and health care utilization (sum of visits during 12 months, categorized as medical or mental health) was extracted through chart review. Results: The majority of veterans reported significant PTSD (72%) and pain (87%) symptoms; 45% received adequate mental health treatment, defined as ≥8 sessions in 12 months. PTSD and the interaction with pain predicted medical utilization; at high pain levels veterans' PTSD severity predicted utilization. PTSD alone predicted mental health utilization. Conclusions: The results show the increased influence of PTSD symptoms on medical health care services when pain ratings are high and suggest the need for interdisciplinary pain clinics that are able to address the overlapping symptoms of pain and common mental health conditions. Implication of results for VA planning are discussed.